DIDACTIC REQUIREMENTS FOR PHYSICAL CULTURE LESSONS - Axmedov Umidjon Usmonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
It is necessary to identify, and understand the pedagogical categories in the regulations on the lessons of Physical Culture, before thinking about the laws of its structure, regardless of whether it will be a school physical education lesson, or a sports activity, a wellness training, whatever the training.